A survey to assess knowledge and acceptability of intrauterine devices (IUD) among family planning clients and providers in the Family Planning services in Cape Town - Van Zijl, Shelsley (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 97-106).